Seasonality of salt foraging in honey bees (Apis mellifera). - Bonoan, Rachael E.; Tai, Taylor M.; Rodriguez, Marlen Tagle.; Feler, Laine.; Daddario, Salvatore R.; Czaja, Rebecca A.; O'Connor, Luke D.; Burruss, Georgianna; Philip T. Starks (Tufts Archival Research Center, 2017)
Honey bees (Apis mellifera) prefer foraging at compound-rich, “dirty”, water sources over clean water sources. Since a honey bee’s main floral diet only contains trace amounts of micronutrients—likely not enough to sustain an entire colony—we hypothesized that honey bees forage in dirty water for physiologically essential minerals that their floral diet, and thus the colony, may lack. While there are many studies regarding macronutrient requirements of honey bees, few investigate micronutrient needs. From 2013-2015, we conducted preference assays in both summer and fall. During all field seasons, honey bees exhibited a strong preference for sodium in comparison to deionized water. There was, however, a notable switch in preferences for other minerals between seasons. Calcium, magnesium, and potassium—three minerals most commonly found in pollen—were preferred in fall when pollen is scarce, but avoided in summer when pollen is abundant. Thus, as floral resources change in distribution and abundance, honey bees similarly change their water foraging preferences. Our data suggest that, although they are generalists with relatively few gustatory receptor genes, honey bee foragers are fine-tuned to search for micronutrients. This ability likely aids the foragers’ search for a balanced diet for the colony as a whole.